Patient assessment of constipation quality of life questionnaire: validity and reliability for Indonesian population - Murdani Abdullah (Medical Journal of Indonesia, 2019)
BACKGROUND Constipation is a condition commonly encountered by physicians, causing a significant reduction in patients’ quality of life. Therefore, successful management of constipation should also include increase the quality of life. The Patient Assessment of Constipation Quality of Life (PAC-QOL) questionnaire is a questionnaire developed to address this issue. However, this questionnaire had not been translated into the Indonesian language. This study was aimed to adapt PAC-QOL into Indonesian culture and perform the psychometric evaluation.